Performance Analysis of Montgomery Multiplier using 32nm CNTFET Technology - N Mathan; S Jayashri; Nurul Ezaila Alias; Michael Loong Peng Tan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
In VLSI design vacillating the parameters results in variation of critical factors like area, power and delay. The dominant sources of power dissipation in digital systems are the digital multipliers. A digital multiplier plays a major role in a mixture of arithmetic operations in digital signal processing applications hinge on add and shift algorithms. In order to accomplish high execution speed, parallel array multipliers are comprehensively put into application. The crucial drawback of these multipliers is that it exhausts more power than any other multiplier architectures. Montgomery Multiplication is the popularly used algorithm as it is the most efficient technique to perform arithmetic based calculations. A high-speed multiplier is greatly coveted for its extraordinary leverage. The primary blocks of a multiplier are basically comprised of adders. Thus, in order to attain a significant reduction in power consumption at the chip level the power utilization in adders can be decreased. To obtain desired results in performance parameters of the multiplier an efficient and dynamic adder is proposed and incorporated in the Montgomery multiplier. The Carbon Nanotube field effect transistor (CNTFET) is a promising new device that may supersede some of the fundamental limitations of a silicon based MOSFET. The architecture has been designed in 130nm and 32nm CMOS and CNTFET technology in Synopsys HSpice. The analysed parameters that are considered in determining the performance are power delay product, power and delay and comparison is made with both the technologies.The simulation results of this paper affirmed the CNTFET based Montgomery multiplier improved power consumption by 76.47% ,speed by 72.67% and overall energy by 67.76% as compared to MOSFET-based Montgomery multiplier.